TLR9-adjuvanted pneumococcal conjugate vaccine induces antibody-independent memory responses in HIV-infected adults - Rasmus Offersen; Jesper Melchjorsen; Søren R. Paludan; Lars Østergaard; Martin Tolstrup; Ole S. Søgaard (Taylor & Francis Group, 2012)
HIV-patients have excess of pneumococcal infection. We immunized 40 HIV-patients twice with pneumococcal conjugate vaccine (Prevnar, Pfizer) +/− a TLR9 agonist (CPG 7909). Peripheral blood mononuclear cells were stimulated with pneumococcal polysaccharides and cytokine concentrations measured. The CPG 7909 adjuvant group had significantly higher relative cytokine responses than the placebo group for IL-1β, IL-2R, IL-6, IFN-γ and MIP-β, which, did not correlate with IgG antibody responses. These findings suggests that CPG 7909 as adjuvant to pneumococcal conjugate vaccine induces cellular memory to pneumococcal polysaccharides in HIV-patients, independently of the humoral response.